Strategies for Using Assistive Technology to Overcome Learning Barriers in Student with Disabillities in Elementary School - Aprilia, Yesinta Dewi; Suwandayani, Beti Istanti; Kuncahyono, Kuncahyono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to identify the implementation of assistive technology in students with learning disabilities and to identify strategies for using assistivetechnology to overcome learning barriers. This research is a literature review (SLR) study conducted on articles from 2013 to 2024 using the Scopus database. The data obtained was saved in *R.I.S. format and synchronized to Reference Manager (Mendeley). Furthermore, VOS-viewer software was used to visualize the data to make the resulting information more interesting and clear. PRISMA flowchart maps the data search process, the number of abstracts screened, and the text retrieved. A total of 8 articles were accessed for this study. The results showed that teachers must prepare themselves well to improve their pedagogical skills by effectively utilizing media and learning resources to achieve the desired goals. Technology or media must adapt teaching materials to the individual needs of students. The results of this study are expected to provide insight into the need for strategies to overcome learning barriers in students with learning disabilities.